Identifikasi dan Kelimpahan Bakteri Enterococcus spp. pada Mucus Karang di Perairan Pemuteran, Bali - Prabaswari, Dewa Ayu Mira; Nurweda Putra, I Dewa Nyoman; Widiastuti, Widiastuti (Journal of Marine Research and Technology; Vol 2 No 1 (2019): FEBRUARI 2019, 2019)
ABSTRACT   DEWA AYU MIRA PRABASWARI. 1414511013. Identification and Abundance of Bacteria Enterococcus spp. on Mucus Coral in Pemuteran Waters, Bali (Supervisor: I Dewa Nyoman Nurweda Putra dan Widiastuti).   Indonesia's geographical location in the area of the world's coral triangle causes the high number of hard coral species. Coral reefs have various functions as habitats of various marine biota such as spawning and natural protection from abrasion hazard. Domestic pollution has a relatively large contribution to coral reef damage. Human activities and river flows carry particulates from land in the form of sediments or organic materials that enter into the sea so that it can lead to the occurrence of pollution of domestic waste. Bacteria Enterococcus spp. is a bacteria found in domestic waste that is used as an indicator of domestic waste pollution. The method of sampling of coral mucus is done by purposive sampling method, where the determination is based on the existence of coral reefs and different coastal conditions. Sampling of coral mucus at each station is by randomly selecting 3 genus of corals in each of 3 replicates of belt 20 x 2 m. Coral mucus samples of 10 ml will be inoculated on Slanetz and Bartley selective media. The presence of Enterococcus spp. which grows on the media is indicated by a colony that grows red. Bacterial identification was analyzed using descriptive analysis, whereas bacterial abundance was analyzed by One Way Anova to determine the difference of bacterial abundance in each station. The result showed that Enterococcus spp. were identified in the dominant coral colonies in Pemuteran waters which sampling stations characterized by the growth of red bacterial colonies on selective media and there was no difference in the abundance of Enterococcus spp. bacteria between different coral genus in each sampling station showing domestic contamination spread evenly on all coral species.